2018
DOI: 10.5005/jp-journals-10078-1234
|View full text |Cite
|
Sign up to set email alerts
|

OutƒPow Facility in Tube Shunt Fenestration

Abstract: Aim: Determination of the effect of varying fenestration technique, and simulated patch graft on outflow facility for Baerveldt tube.Materials and methods: Silicone tubing similar to Baerveldt implant (AMO, Santa Ana, CA) with different fenestrations techniques was connected to a digital manometer in a closed system with a fluid-filled syringe on a stand to adjust pressure. The venting slits included: (A) 4 piercings with 7-0 TG140-8 needle; (B) a 2-mm slit with a 15º blade; (C) 4 piercings with a 15º blade; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Like other reports evaluating glaucoma tube shunt fenestrations, our results varied widely between each trial. [ 7 , 8 ] This may be due to microscopic variations in surgical technique resulting in a variety of differences in microarchitecture between fenestrations [Figure 2]. We found that fenestrations with the 7-0 Vicryl TG140-8 needle could take the form of a uniplanar, biplanar, or triplanar structure.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Like other reports evaluating glaucoma tube shunt fenestrations, our results varied widely between each trial. [ 7 , 8 ] This may be due to microscopic variations in surgical technique resulting in a variety of differences in microarchitecture between fenestrations [Figure 2]. We found that fenestrations with the 7-0 Vicryl TG140-8 needle could take the form of a uniplanar, biplanar, or triplanar structure.…”
Section: Discussionmentioning
confidence: 95%
“…Olayanju et al characterized the outflow facility of a tube system with constant intraocular pressure and fenestrated with varying needles and blades. [ 8 ] They found that the outflow facility (mL/min/mmHg) was mainly dependent on intraocular pressure and did not significantly change by external weight on the tube (e.g., scleral patch graft). However, they made the observation that the microarchitecture of the fenestrations was widely variable; the same external forces (e.g., scleral patch graft) could either reinforce fenestration closure or hold the fenestrations open.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations